Alfalfa response to different water availability - Cunha, Gilberto Rocca da; Bergamaschi, Homero; Paula, José Roberto Faleiro de; Saibro, João Carlos de (Pesquisa Agropecuaria Brasileira, 1998)
A study was made with alfalfa (Medicago sativa L.), cv. Crioula, planted in June 1989 (0.3 m between lines), in the EEA-UFRGS, in Eldorado do Sul (30º5'S, 51º39'W at 46 m of altitude) in order to evaluate the response of the culture to water, and its interaction with the availability of phosphorus (P). The aspersion in line system was utilized, involving six water layers (precipitation + irrigation) and three doses of P (one, two and four times the recommended in accordance with soil analysis). The total yield of dry matter from four cuttings in the spring-summer period, from October 1989 until March 1990, was significantly affected only by the thickness of the water layer. The total yield of dry matter associated with the greater thickness of the water layer (716.9 mm) was 115% superior to the total yield associated with the lesser thickness of the water layer (524.4 mm). A quadratic (r2 = 0.996) crop-water production function was developed, equating the dry matter of alfalfa, in the spring-summer period, to the water layer.